The Cost of Success: Exploring the Impact of Textbook Costs at a Hispanic-Serving R1 Institution - Leo S. Lo; Jennifer Jordan; Holly Surbaugh (Open Praxis)
The cost of textbooks is a significant concern for undergraduate students, particularly at institutions serving marginalized populations. This study explores this issue at the University of New Mexico, a Hispanic-Serving R1 institution. A comprehensive survey was conducted among undergraduate students to understand their perceptions of textbook costs and its impact on their academic success. The survey covered aspects such as the perceived reasonableness of costs, budgeting practices, and strategies to manage expenses. The results revealed that high textbook costs significantly affect students’ financial well-being and academic success. Many students perceive these costs as unreasonable, leading to financial strain. Students employ various strategies to manage these expenses, including purchasing from vendors other than the campus bookstore, renting, or sharing books with classmates. This study underscores the need for enhanced support and resources to alleviate the financial burden of textbook costs on students, contributing valuable insights to the literature on this subject.